Akulturasi Minangkabau - Melayu Melalui Musik dan Tari di Batu Bara Sumatera Timur - Yusuf, Muhammad (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2020)
The entry of the Minangkabau ethnicity in North Sumatra, especially in East Sumatra, is not just a population migration. This migration also had an impact on the acculturation of culture, one of which was music and dance. This researcher focuses on the acculturation of Malay and Minangkabau culture on the Bansi musical instrument and the Gobuk Melayu dance. This research was conducted in order to find the roots and how acculturation can occur. In this research, the research method used is descriptive quantitative research. It is hoped that from this research, other similar studies will be born and dig deeper into the forms of acculturation in North Sumatra, especially East Sumatra.Keywords: acculturation,Minangkabau, Malay, East Sumatera